FACTORS THAT AFFECT THE LEVEL OF SATISFACTION OF OUTPATIENT SERVICES IN PAKIS HEALTH CENTER FERN MALANG - Siti, Patimah; Nurdina; Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2018)
The clinic is an implementation functional unit that has authority and responsibility for the maintenance of the public health in the region. The aim of this research is to know the factors that affect the level of satisfaction of outpatient Clinics in Pakis, Malang. This research design is descriptive quantitative that using the approach of cross sectional. This research was obtained as many as 205 respondents in Clinics Fern Malang. This study used two independent variables namely variables ((X 1), Facilities and infrastructure (X 2), human resources (X 3)), and the dependent variable i.e. patient satisfaction (Y). The data collection was done in the primary study. The research results obtained based on the age of the most aged 20-29 years i.e. 24% (50 respondents). Based on the job obtained most of the work as the IRT (Housewife) 42% (87 respondents). Indigo variable significance facilities of clinics of 0.018, variable and infrastructure of 0.000, and variable HR of 0.002. On the health facilities of the variable indicates that significant 0,018 < 0.05, inferred that the Ha received means the positive effect of clinics and facilities significantly to the level of satisfaction of outpatient Clinics in Fern Malang. The satisfaction of patient is a very valuable asset because when patients are satisfied they will continue to make choices against usage of the service, but if the patient did not feel satisfied they will tell to others about the bad experience. In fact, clinic with such good service will influenced the result in the emergence of satisfaction, loyalty, and even supports the implementation of the strategy of clinics as well as the achievement of the vision and mission of the clinic.